HUTSULSHCHYNA IN THE STORY OF MARKO CHEREMSHYNA «KERMANYCH»: COMMON GROUND WITH YURIY FEDKOVYCH - Vasylchuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Introduction. Classic of Ukrainian literature Marko Cheremshyna (autonym Ivan Semanyuk 1874-1927) born in Hutsul village Kobaky, Kosiv region. He is inseparable from the life of the people of his native land, Hutsulshchyna. The writer managed to go beyond the boundaries of regionality and took one of the most honorable places in Ukrainian literature at the end of 19th century and the first quarter of the 20th century. The debut book of works of Marko Chermshyna was a collection of short stories "Karby" (1901). Though as a litterateur he had made his debut story ‘Kermanych’ (1896). This work is a source for understanding of the first steps of Marko Chermshyna in the literature. It is the basis for conversations about the imitation and originality of the young writer. Purpose. Purpose of the article is to show the features of artistic reflection of Hutsulshchyna in the story of Marko Cheremshyna ‘Kermanych’ as well as consider the "common ground" with the creativity of Yuriy Fedkovych. Originality. Taking into account the experience of previous researchers (Mykola Zerov, Oleksa Zasenko, Roman Pikhmanets, etc.), a new attempt was made to read out the features of the vision of Hutsulshchyna by young Marko Cheremshyna in the article. It is noted that the author's appeal to the topic of Hutsulshchyna was organic and logical, because it did not require the additional entry of the writer in the realities, problems and themes of the region. Through an appeal to the writer's biography, using memoirs, as well as a comparison of the vocabulary of the writings of both writers give an answer to the question about the ways of Yuri Fedkovich's influence on the young Marko Cheremshyna. Results. The object of the study was the story of Marko Cheremshyna "Kermanych". It is indicated on the peculiarities of the vision of Hutsulshchyna by a young author. It is revealed that the mediated influence of Yuriy Fedkovych is noticeable in the interpretation of Hutsulshchyna by Marko Cheremshyna . Marko Cheremshyna came to the literature with a sense of belonging to the writer Yuri Fedkovich, with whom his father was acquainted and often talked about him. In his creative world, there is also an emphasis on the areas associated with Yuriy Fedkovych. Partly pretended and partly real youthfulness of the main character, Ivan Sain, is shown in the story "Kermanych". The writer noticed a typical feature of Ukrainian hutsuls, the desire to be better and more skillful than other. And this feature of the manner of Hutsuls plays a key role in the fate of the hero. Ivan Sain calls himself a kalfa-helmsman. Yuriy Fedkovych calls Olexa Dovbush kalfa in his works. But the word "kalfa" is not recorded in Hutsulshchyna. In Turkish, it is used to mark someone senior (in particular, "kalfa" means the main servant, the nurse in the Sultan Harem). The author of the article suggests that this word, which is typical of the works of Bukovynian, Yuriy Fedkovych (Bukovyna was a part of the Ottoman Empire), got to Marko Cheremshyna in Galicia as a result of direct communication between Yuriy Fedkovych and the father of the writer. So it can serve as one of the "common ground" between Yuriy Fedkovych and Marko Cheremshyna. In general, the author of the article notes the good knowledge of the writer of the folklore and ethnographic color of Hutsulshchyna, which also found a vivid reflection in the text of the story. The stubborn nature of the character of the story is designed by the writer on an unburied Hutsulriver, Cheremosh, which carried forest transportation. There is also a social motive when strangers exploited the natural resources of the Carpathians. Ivan Sain died for other people's interests by fusing logs belonging to one of these exploiters. Conclusion. The story "Kermanych" has signs of the romantic outlook of the author with elements of sentimentality. The writer widely uses the Hutsul dialect with its characteristic vocabulary and diminutively caressing forms. Marko Cheremshyna realized that the material of life that he owns as a native of Hutsulshchyna could be used to create original texts about this region of the Carpathians what is precisely the influence of Yuriy Fedkovych on Marko Cheremshyna.